M2 macrophage-derived exosome-modified bioprosthetic heart valves with enhanced anti-inflammatory, anticoagulant and anticalcification properties - Jingruo Chen; Shufen Li; Xiaoting Chen; Tianyi Qu; Ming Chen; Zheng Chai; Weihua Zhuang; Wenchuang (Walter) Hu; Mao Chen (Materials & Design)
Glutaraldehyde (Glut) cross-linked bioprosthetic heart valves (BHVs) have shown great performance in the replacement treatment of severe valvular heart diseases in recent years due to the rapid development of transcatheter aortic valve replacement (TAVR) and the aging population. However, the durability of BHVs suffers from inflammation, limited endothelialization, thrombus formation and calcification during clinical application, which makes it urgently to prolong the service life of BHVs. To this end, we introduced exosomes derived from M2 macrophages to the surface of Glut cross-linked bovine pericardium (Glut-BP) to develop a novel kind of BHVs, namely M2-EXO-BP, to improve the durability of Glut-BP. Compared with Glut-BP, M2-EXO-BP presented significantly improved biocompatibility and endothelialization. Moreover, M2-EXO-BP also reduced the adhesion of platelets and the formation of thrombi during the ex-vivo arterial-venous blood circulation experiment. In addition, calcification of M2-EXO-BP after 60 days of subcutaneous implantation in SD rats was obvious reduced compared with Glut-BP. Importantly, in vitro and in vivo studies confirmed that M2-EXO-BP could efficiently reduce inflammation levels compared with Glut-BP. In summary, these results suggest that BHVs modified with exosomes from M2 macrophages might be an interesting strategy to improve the durability of BHVs.